Neuronal Circuits Involved in Emotion Activation - Popa, Georgeta Mioara (New Trends in Psychology, 2022)
Modern science supports the classical perspective on emotion, namely that in our brain there are several circuits of emotion and each produces a specific set of changes. Emotions are the result of a combination of the physical properties of our body, a flexible brain that is connected to the environment in which it develops, the environment being created by our culture and education. Emotions are considered reflexes in conflict with our own judgment: the primitive part of the brain pushes us out of pragmatics but the rational part forces us to refrain. This inner confrontation between emotion and reason, defines us as human beings. An overview of emotion processing is provided by the Scherer model, which involves five basic, coordinated and synchronized components. The mechanism of primary emotions is followed by mechanisms of secondary emotions, which occur after the correlation between experienced feelings, categories of objects and situations, and primary emotions.